8. OUTCOMES OF MINIMALLY INVASIVE MICROSURGERY FOR RUPTURED CEREBRAL ANEURYSMS (Vietnam Journal of Community Medicine, 2024)
Object: To evaluate surgical outcomes of patients with ruptured middle cerebral artery aneurysm treated by minimally invasive surgery.Research objects and methods: Prospective study at Bach Mai Hospital from January 2021 to June 2023. Patients with ruptured middle cerebral artery aneurysm, whose sum of WFNS clinical grade and Fisher’s subarachnoid hemorrhage grade was less than or equal to 5 were treated by surgical clipping of aneurysm through mini-pterional approach. Pre-operative conditions, features on CT angiography, complications, neurological outcomes and patients’ satisfaction were evaluated.Results: 62 patients (24 males and 38 females), mostly aged 50-70, were enrolled in the study. Most frequent symptoms include headache and meningeal irritation. Aneurysm occlusion rate was 98.39%. 93.55% of patient had good clinical outcome (mRS 0-2). Most patients were satisfied with the cosmetic results and level of craniotomy-related pain.Conclusion: With thorough patient selection, minimally invasive surgery can be a good option for ruptured middle cerebral artery aneurysms.
Keywords: Middle cerebral artery aneurysms, subarachnoid hemorrhage, minimally invasive surgery.